Mycobacterial 65-kilodalton heat shock protein induces tumor necrosis factor alpha and interleukin 6, reactive nitrogen intermediates, and toxoplasmastatic activity in murine peritoneal macrophages. - Peetermans, W E (1995)
The 65-kDa heat shock protein (Hsp65) is supposed to play a role in host defense against infections with various microbial pathogens and in autoimmune inflammatory disorders. These effects are thought to result mainly from an Hsp65-specific T-lymphocyte-mediated immune response that recognizes conserved epitopes. The aim of the present study was to assess whether mycobacterial Hsp65 has a direct effect on resident murine peritoneal macrophages, independent of Hsp65-sensitized T lymphocytes. Exposure of peritoneal macrophages from naive C57BL/6 mice to the mycobacterial Hsp65 in vitro induced an enhanced release of tumor necrosis factor alpha (TNF-alpha) and interleukin 6. These cells also produced large amounts of reactive nitrogen intermediates (RNI) and inhibited the intracellular proliferation of Toxoplasma gondii. Small amounts of gamma interferon acted synergistically with Hsp65. Thus, exposure of murine macrophages to Hsp65 results in activation of these cells. The acquisition of these characteristics by peritoneal macrophages occurred in the absence of sensitized T lymphocytes. Addition of anti-TNF-alpha antiserum resulted in an attenuation of the Hsp65-induced release of RNI and toxoplasmastatic activity, indicating that endogenous TNF-alpha is involved in the Hsp65-induced macrophage activation. The conclusion of this study is that in vitro exposure of peritoneal macrophages to the mycobacterial Hsp65 induces the release of proinflammatory cytokines and RNI and results in inhibition of the intracellular proliferation of T. gondii. These effects on murine macrophages occur independently of Hsp65-specific T lymphocytes. The proinflammatory effect of Hsp65 demonstrated in this study suggests that this heat shock protein may play a role in the initiation of inflammation that adds to a non-species-specific resistance in the early stages of infections.